Laparoscopic adrenal cystectomy - report of two cases - Hossain, GM Zakir; Rahman, Mofizur; Hasan, Mohammad Rashedul (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: laparoscopic; adrenal cystectomy doi: 10.3329/jcmcta.v19i1.3854 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):50-53